2021
DOI: 10.3390/app11156809
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of RC Beams Strengthened with Fe-Based Shape Memory Alloy Strips Using the NSM Method

Abstract: This paper presents a finite element (FE) analysis for predicting the flexural behavior of reinforced concrete (RC) beams strengthened with Fe-based shape memory alloy (Fe-SMA) strips using a near surface mounted (NSM) method. Experimental results reported in the literature were used to verify the proposed FE model. FE analyses were conducted using OpenSees, a general-purpose structural FE analysis program. The RC beam specimens were modeled using a nonlinear beam-column element and a fiber element. The Concre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…However, most of the research for the application of Fe-SMA to the construction field has focused on application for strengthening deteriorated RC structures or evaluating the mechanical properties of Fe-SMAs [19][20][21][22][23]. Very little research has been devoted to evaluating the applicability of Fe-SMA materials as reinforcement for new structures.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the research for the application of Fe-SMA to the construction field has focused on application for strengthening deteriorated RC structures or evaluating the mechanical properties of Fe-SMAs [19][20][21][22][23]. Very little research has been devoted to evaluating the applicability of Fe-SMA materials as reinforcement for new structures.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that prestressed reinforcement with SMA could obviously increase the cracking load, improve the fatigue resistance, and reduce the crack width and mid-span deflection of concrete beams. Then, Yeon et al [74] used OpenSees software (https://opensees.berkeley. edu/) to conduct finite element modeling and analysis of the reference [72], verified the validity of the finite element model, and studied the influence of concrete strength, level of reinforcement, and number of Fe-SMA strips on the bending behavior of RC beams.…”
Section: Flexural Performancementioning
confidence: 99%
“…It was found that prestressed reinforcement with SMA could obviously increase the cracking load, improve the fatigue resistance, and reduce the crack width and mid-span deflection of concrete beams. Then, Yeon et al [ 74 ] used OpenSees software ( ) to conduct finite element modeling and analysis of the reference [ 72 ], verified the validity of the finite element model, and studied the influence of concrete strength, level of reinforcement, and number of Fe-SMA strips on the bending behavior of RC beams. In addition, Canadian scholars Rojob and El-Hacha [ 75 , 76 ] conducted experimental studies on the flexural properties of prestressed RC beams strengthened with NSM Fe-SMA reinforcement in long-term freeze–thaw cycles and under fatigue load conditions, as shown in Figure 10 b.…”
Section: The Application Of Sma In Structural Components Of Buildingmentioning
confidence: 99%
“…The free length can then be filled with mortar after cooling. Several investigations have been conducted on the feasibility and short-term behavior of RC elements strengthened with FeSMA, including experimental bond behavior [17][18][19][20][21], lab-scale beam tests [10,[22][23][24][25][26], numerical (based on non-linear finite element analysis) studies [27][28][29][30][31][32][33], and real-world applications [34,35]. Other noteworthy applications include the use of Fe-SMA for shear strengthening of RC beams [36], strengthening of masonry walls [37] and self-centering columns [20,38].…”
Section: Introductionmentioning
confidence: 99%